Keratan sulfate exacerbates experimental autoimmune encephalomyelitis. Issue 12 (5th September 2015) - Ueno, Rino; Miyamoto, Katsuichi; Tanaka, Noriko; Moriguchi, Kota; Kadomatsu, Kenji; Kusunoki, Susumu
Abstract : Proteoglycans (PGs) are the components of extracellular matrices in the central nervous system (CNS). Keratan sulfate (KS) is a glycosaminoglycan that is included in the KSPG that acts as an inhibitory factor in nerve regeneration after CNS injury. To investigate the role of KS in immune diseases, we induced experimental autoimmune encephalomyelitis (EAE) in mice that were deficient in the N‐acetylglucosamine (GlcNAc)‐6‐O‐sulfotransferase 1 (GlcNAc6ST1) gene (KS‐KO). KS‐KO mice developed less severe EAE and showed repressed recall response in the induction phase. Furthermore, GlcNAc6ST1 might have roles in the passage of the pathogenic lymphocytes through the blood–brain barrier via adhesion molecules. Thus, modulation of KS may become a treatment for neuroimmunological diseases. © 2015 Wiley Periodicals, Inc. Abstract : Keratan sulfate (KS) is a major proteoglycan and is involved in the pathogenesis of experimental autoimmune encephalomyelitis. Modulation of KS may become a treatment for neuroimmunological diseases.